The Relationship Between Medical Treatment and Survival Rates Among Cervical Cancer Patients at Dr. M. Djamil General Hospital in Padang, 2020–2024 - Hasanah, Pujatul; Djafri, Defriman; Masnarivan, Yeffi; Syafrawati, Syafrawati (Jurnal Kesmas Jambi, 2026)
Medical treatment for cervical cancer aims to improve survival, cure the disease, and prolong patients’ life expectancy. Cervical cancer treatment consists of surgery, radiation/radiotherapy, chemotherapy, or a combination of these three modalities, depending on the extent and stage of the disease. This study aims to analyze the relationship between medical treatment and the survival of cervical cancer patients at Dr. M. Djamil General Hospital, Padang, during the period 2020–2024. This study used a representative cohort design utilizing medical record data from Dr. M. Djamil General Hospital, Padang, of patients who underwent medical treatment from 2020 to 2024. Samples were selected using a simple random sampling technique, with a total of 121 samples. Data were analyzed through univariate, bivariate (Kaplan-Meier and Cox Regression), and multivariate. The results showed that among 121 patients, 57.0% underwent combination medical treatment. Based on patient characteristics, 90.9% were aged >35 years, 87.6% had an education level ≤ senior high school, 74.4% were unemployed, and 56.2% were in the advanced stage of disease. The association between type of medical treatment and survival showed a p-log rank value of 0.003 (<0.05), indicating that at least one type of medical treatment had a different survival outcome compared to the others. Based on survival analysis, a difference in survival was only found between radiotherapy and combination treatment. This study found differences among types of medical treatment in relation to the survival of cervical cancer patients.